(untitled) (Asian Journal of Pharmaceutics (AJP), 2014)
Ciprofloxacin is a broadâ€spectrum antiâ€infective agent of the fluoroquinolons. It has activity against periodontal pathogens. Saccharin is one of the most widely used artificial sweetening agents. The complex of ciprofloxacin saccharinate was prepared to improve organoleptic properties of ciprofloxacin and it was characterized using fourier transform infrared analysis,differential scanning calorimetric, photomicrographs, solubility determination of the complex and ultravioletâ€scanning in different media as well as determination of the actual drug content. Eight formulations of ciprofloxacin saccharinate bioadhesive dental films were prepared using chitosan, carbopol 934, and hydroxypropyl methyl cellulose (HPMC). The prepared films were evaluated for their physicâ€mechanical properties including film thickness, weight uniformity, and tensile strength, folding endurance, surface pH, and percentage elongation. In addition, mucoadhesive performance of films, drug content and in vitro release of ciprofloxacin from different films were determined. The best formulations were selected and were subjected to stability study at 40Â°C and 75% relative humidity for 3 months and microbiological test. Results revealed that the use of mixture of carbopol and HPMC with chitosan improved physical and chemical properties of the prepared films. Microbiological results showed that, F7 had the highest inhibition zone which may be due to the presence of high concentration of carbopol 934 that leads to high mucoadhesive time.